Nursing Students' Protective Behaviors towards COVID-19, their Perception of Information, and the Psychological Effects in the Early Stages of the Pandemic - Kübra Pınar Gürkan; Burcu Cengiz (Association of Nurse Managers, 2022)
Aim: The pandemic has psychological effects on all people and the risk of death due to COVID-19. Future nurses are expected to be as prepared as possible for public health emergencies such as the pandemic. This study was conducted to determine nursing students' protective behaviors from COVID-19 and the psychological effects of the pandemic. Method: A descriptive and cross-sectional design was used in this study. The sample of the study consisted of 685 nursing students in Turkey. Results: The students followed the news about COVID-19 on social media and TV, and their perception of information was moderate. The anxiety levels of female students were higher, and those with a family history of chronic diseases were more psychologically affected by the pandemic than those who did not. As the number of individuals with chronic diseases in the family increased, anxiety levels also increased. It was determined that students showed protective behaviors such as social distance and mask use in the early stages of the pandemic. Conclusion: Nurses of the future will be involved in protecting and promoting health and treating illness as an important professional group in the health care system. Identifying mental health and psychological needs during the pandemic will be an important contribution to the management of the pandemic.